Pierre Leriche (ed). Art & Civilisations de l’Orient Hellénisé: rencontres et échanges culturels d’Alexandre aux Sassanides. - Moodie, Meg (Journal of Greek Archaeology, 2017)
The growing interest in the eastern part of the Hellenistic world has resulted in a number of recent papers, conferences, and books discussing the ebb and flow of cultural contact in previously under-explored regions. Developed from an international colloquium held in September 2009, this edited volume attempts to give an overview of as well as introduce new approaches to understanding the cultural engagement in the Hellenistic East ‘from Alexander to the Sassanids’. No mean feat, the book covers a variety of topics in 30 short chapters in both French and English, giving a true impression of the internationality of this work.